Lokelma's Interaction With Computed Tomography Angiography - Rhett Boss; Max Nguyen; Sandhya Wahi-Gururaj (Annals of Internal Medicine: Clinical Cases)
A hospitalized 58-year-old man with hyperkalemia received oral Lokelma. Computed tomography angiography was performed due to concern for gastrointestinal (GI) bleeding, which demonstrated radiopaque material throughout the GI tract, even though no oral contrast had been administered. We present the second case, to our knowledge, describing Lokelma's radiopaque properties and the first, we believe, in the setting of GI bleed.